Pengaruh Substitusi Silase Isi Rumen Dengan Persentase Yang Berbeda Dalam Pakan Buatan Terhadap Efisiensi Pakan, Pertumbuhan Dan Kelulushidupan Benih Ikan Mas (Cyprinus carpio) - Muslim, Abdul Jamil; Hutabarat, Johanes; Arini, Endang (Journal of Aquaculture Management and Technology, 2013)
One of the alternative raw material that has not been widely used as a feed composition and not compete with other food needs is rumen waste. Rumen waste can be used as an alternative material for the manufacture of feed. This purpose of this study is to review the Substitution effect of adding silage of rumen contents in the artificial feed to the efficiency of feed utilization, protein efficiency ratio, the relative growth rate, and survival rate of carp juvenile. The method used in this research is experimental method. The material used is a carp juvenil with an average individual weight of 0.9 to 1 g. The experimental design used was completely randomized design (CRD) with 4 treatments with three replications each. Feed given 3 times a day in the morning at 07.00, 13.00, and 16.00. Substitution silage rumen contents amounted of A (0%), B (5%), C (10%) and D (15%). Artificial feed in the form of pasta that will be given to the maintenance of carp seed. The variables measured were EPP, PER, RGR and SR. EPP values for treatments A, B, C, and D, respectively, 34.26%; 43.64%; 39.04%, and 37.47%.PER values for treatments A, B, C, and D, respectively, 0,92; 1,33; 1,22; and 1.12. RGR values for treatments A, B, C, and D, respectively, 1,65%; 2,36%; 2,03%; and 1,78% / day. SR values for all treatments A, B, C, and D is 100%. Water quality values for all the treatment that the water temperature from 23.2 to 24.4 Â° C, pH 6.93 to 7.57, DO 6.98 to 7.40 mg / L, and ammonia 0.56 to 0.99 mg / L. The results show the percentage of silage substitution content different significant result (P 0.05) to SR carp juvenile.